Physiological effects of strobilurin and carboxamides on plants: an overview - Amaro, Amanda Cristina Esteves [UNESP]; Baron, Daniel; Ono, Elizabeth Orika [UNESP]; Rodrigues, João Domingos [UNESP] (Springer Nature, 2020)
Usually, fungicides are used to control and prevent diseases, however, a group of fungicides called strobilurins has brought about a new possibility of use for these products: the physiological effects. This group of fungicides modifies the plant physiology, through changes in metabolism and growth, which increases crop yield. Another group of fungicides, which also reveal physiological effects, is carboxamides. However, there are still only a few publications in scientific journals regarding the effects of the molecules of this group, since they were just introduced in the market recently. The carboxamides when applied together with or alternately to strobilurins potentiate their action. Both are systemic fungicides that operate preventively and have a little curative effect, but the preventive application of these products yields benefits, in addition to protecting the plant by increasing production through its physiological benefits. The physiological effects detected when applying strobilurins or carboxamides in healthy plants are due to the increase in net photosynthesis (true photosynthesis minus dark respiration and photorespiration), as it temporarily reduces plant respiration, which led to less carbon dioxide loss and, consequently, generates more energy for the plant. Besides, the increase in antioxidant enzymes provokes increased tolerance to stress. It also results in higher activity of nitrate reductase and a better hormonal balance, increasing the synthesis of indolyl acetic acid (IAA) and abscisic acid (ABA), as well as reduced ethylene production, delayed senescence and prolonged photosynthetic efficiency, known as green effect. These effects, together, increase productivity and fruit quality.
Keywords: Boscalid; Carboxamide; Pyraclostrobin; Strobilurin